Evaluating power efficient algorithms for efficiency and carbon emissions in cloud data centers: a review - Uddin, Mueen; Darabidarabkhani, Yasaman; Shah, Asadullah; Memon, Jamshed (Elsevier, 2015)
A data center comprises of servers, storage devices, cooling and power delivery equipment to support other components, exchange data and information to provide general services such as software-as-a-service (SaaS), Platform-as-a-Service (PaaS)and Internet-as-a-Service (IaaS). Data center require massive amount of computational power to drive complex systems. In return these massive systems bring many challenges and concerns including power dissemination and environmental sustainability. Higher power demand in data centers and changes in computing technology together to maximize data center performance has led to deploying multitude methods to estimate power intensity. Energy cost increment, global economic downturn, and global warming and other concerns have resulted in new research in achieving power efficient data centers.